The protective effects of Clerodendranthus spicatus (Thunb.) C. Y. Wu extract on oxidative stress induced by 2,2'-azo (2-methylpropamidine) dihydrochloride in HL-1 mouse cardiomyocytes - Li, Ying; Wang, Jia; Jiang, Jiahui; Li, Xiang; Wang, Ming (Frontiers in Cardiovascular Medicine, 2022)
To investigate the protective effects of Clerodendranthus spicatus (Thunb.) C. Y. Wu extract (CSTE) on oxidative stress injury in HL-1 mouse cardiomyocytes induced by 2,2'-azo (2-methylpropamidine) dihydrochloride (AAPH, 1 mmol/L), HL-1 cells were co-cultured with different concentrations (10–100 μg/mL) of the CSTE for 24 h. A cell damage model was established by continuously culturing the cells in Dulbecco's Modified Eagle Medium plus AAPH for 4 h. Cell survival rates were measured by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide assay, and by measuring intracellular malondialdehyde (MDA) content. MDA and total reactive oxygen species (ROS) levels were determined by thiobarbituric acid colorimetry and the 2',7'-dihydrodichlorofluorescent sodium yellow diacetate probe, respectively. Apoptosis was measured by flow cytometry. The intracellular catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), glutathione s-transferase (GST), γ-glutamylcysteine synthetase (γ-GCS), and glutathione (GSH) contents were determined by colorimetric methods. CSTE content was determined by high performance liquid chromatography. The CSTE pretreatment improved survival rates in damaged HL-1 cells, reduced total intracellular ROS and MDA levels, and reduced apoptosis. The CSTE also increased the activities of the antioxidant enzymes (CAT, SOD, GSH-Px, and GST), as well as the γ-GCS and GSH levels in damaged cells. Real-time fluorescence quantitative polymerase chain reaction analysis indicated that the CSTE upregulated CAT, SOD1, and GSH-Px mRNA expression levels. Additionally, the CSTE reduced MDA and ROS levels in HL-1 cells by improving the endogenous antioxidant system; thus, alleviating the oxidative stress damage caused by AAPH. Our compositional analyses revealed that the CSTE contained caffeic acid, isoquercetin, rosmarinic acid, luteolin, and baicalin. The CSTE demonstrates antioxidant and protective effects in myocardial cells.